2012
DOI: 10.1093/geront/gns125
|View full text |Cite
|
Sign up to set email alerts
|

The High Cost of the International Aging Prisoner Crisis: Well-Being as the Common Denominator for Action

Abstract: The aging prisoner crisis continues to gain international attention as the high human, social, and economic costs of warehousing older adults with complex physical, mental health, and social care needs in prison continues to rise. According to the United Nations, older adults and the serious and terminally ill are considered special needs populations subject to special international health and social practice and policy considerations. We argue that older adults in prison have unique individual and social deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 17 publications
0
77
1
Order By: Relevance
“…Literature on the healthcare of prisoners, and older prisoners in particular, is limited [5], although a gradual increase is evident from studies published in medical [1,3], gerontology [8,9,10,11,12] and public health journals [13,14,15]. These and other studies provide new knowledge pertaining to disease burden and the quality of healthcare received by prisoners.…”
Section: Introductionmentioning
confidence: 99%
“…Literature on the healthcare of prisoners, and older prisoners in particular, is limited [5], although a gradual increase is evident from studies published in medical [1,3], gerontology [8,9,10,11,12] and public health journals [13,14,15]. These and other studies provide new knowledge pertaining to disease burden and the quality of healthcare received by prisoners.…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent the prediction, however, sheltered housing with community-based support teams is the best choice in our knowledge [31,33]. Welfare costs might increase for elderly prisoners temporarily, but the cost will be balanced out after they live in the community and work regularly [32,35]. Furthermore, their lifestyles without deprivation are invaluable and could safeguard their human rights [13].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, a temporary house with care management could prevent aging prison people from reoffending. Previous studies reported a temporary house with care management for aging prison people, but did not report recidivism rates [35]. The present study examined the effects of a temporary house with case management on recidivism rates in a Japanese prison.…”
Section: A Reintegration Program For Elderly Prisoners Reduces Reoffementioning
confidence: 91%
“…In particular, geriatric forensic social workers are well positioned to prevent or intervene with the aging and dying in prison issue because of combined generalist and specialized practice knowledge and skills. Given this current crisis, a two-pronged approach to clinical and policy practice in diverse settings, such as prisons, and with diverse populations, such as incarcerated older people is necessary (Maschi et al 2013). For example, in many of the research, practice, and policy recommendations noted in the Office of the Inspector General's report (2015), social workers can play a role in addressing all of them.…”
Section: Discussion Implications For a Human Rights Approach To Sociamentioning
confidence: 99%